Canine Pyometra – A Review - Bhavya Charitha, B.V.S.; G.Chaitanya; M.G.Jayathangaraj; Deepti Chandaka (The Indian Veterinary Journal, 2026)
Pyometra is frequently found as one of the clinical problems of the female reproductive system in the bitches. It is one of the life-threatening conditions, requiring immediate medical attention. The frequent causes for the occurrence of pyometra in female dogs often include hormonal imbalances in the bitches as well as pathogenic bacterial species like E. coli organisms. Further, other miscellaneous etiological agents like cysts in the uterus, thickened uterine wall, etc., were also implicated in pyometra. The frequent occurrence of clinical symptoms of multiple organ dysfunction, especially those related to the renal system, is also dealt with. The pathogenesis-related information has also been dealt with. Various symptoms like persistent vomiting, signs related to deranged renal functions, anorexia, lethargy, etc., have been detailed. The different treatment measures associated with the administration of drugs like Cabergoline, Cloprostenol, Mifepristone, etc., have been dealt with apart from the prophylactic measures.